The Borneo Islamic Heritage and The Significance of Idahan Jawi Manuscript - Suraya Sintang; Rosdiana Onga; Siti Aidah Hj Lukin; Asmady Idris (Al-Albab, 2020)
Borneo Island is the third largest island in the world, rich in natural resources, biodiversity and cultural diversity. The uniqueness of Borneo is that it is home to three countries; Malaysia, Indonesia and Brunei Darussalam, each with their own valuable cultural heritage. One of the unique aspects of the Borneo archipelago is the shared wealth of civilizations derived from the dissemination of Islam. Treasures known as the “Borneo Islamic Heritage" are not only valuable as cultural artefacts that need to be preserved, but they can also be elevated and commercialised as regional economic drivers. This paper discusses the Idahan manuscript written in Jawi script as one of the treasures of Islamic intellectual legacy in Borneo. The method of study is based on content analysis which depicts the descriptive history of the discovery of the Idahan Jawi manuscript. This manuscript not only serves as evidence of the early embrace of Islam in Sabah, but also as a reference to matters pertaining to religion and the laws of Islamic jurisprudence. This factor leads the Idahan community be considered as the first native people embracing Islam at the east coast of Sabah. The contribution of this study is to enhance understanding of the development of Islamic heritage in Borneo Island and to inculcate the spirit of solidarity among the people living in the region.